Comparative Analysis of Surgical Outcomes of Flexible Ureteroscopy and Da Vinci Robotic Surgery in Community Patients with Renal Pelvic Stones Larger than 2 cm - Yu-Ju Yeh; Shu-Chuan Weng; Yu-Hsiang Lin; Chien-Lun Chen; Shu-Han Tsao; Han-Yu Tsai; Horng-Heng Juang; Phei-Lang Chang; Chen-Pang Hou (Medicina, 2023)
Background and Objectives: This study evaluated and compared the surgical outcomes of retrograde intrarenal surgery (RIRS) lithotripsy versus robot-assisted laparoscopic pyelolithotomy (RAPL) in community patients with renal pelvic stones larger than 2 cm. Materials and Methods: A total of 77 patients who underwent RIRS (RIRS group, n = 50) or RAPL (RAPL group, n = 27) at our institution between December 2016 and July 2022 were recruited. A single surgeon performed all surgical operations. Preoperative, operative, and postoperative data were recorded. The study evaluated various clinical outcomes, namely, urinary tract infections, analgesic use, emergency room readmissions, stone clearance rates, surgical complications, and medical expenditures associated with the treatment courses, and compared them between the groups. Results: The RAPL group had a larger mean stone diameter and higher degree of hydronephrosis than the RIRS group did. The RIRS group had superior outcomes regarding operative time, length of postoperative hospital stay, surgical wound pain, and medical expenditures. Regarding postoperative outcomes, comparable rates of postoperative urinary tract infection, prolonged analgesic use, and emergency room readmissions were observed between the groups. However, the RAPL group had a higher stone clearance rate than the RIRS group did (81.5% vs. 52.0%, p = 0.014). Conclusions: For the surgical treatment of renal pelvis stones larger than 2 cm, RAPL has a superior stone clearance rate than RIRS; however, RIRS achieves superior outcomes in terms of medical expenditures, length of hospital stay, and surgical wound pain. Both procedures were equally safe.